2011
DOI: 10.1128/jcm.02039-10
|View full text |Cite
|
Sign up to set email alerts
|

Are Nasal Carriers of Staphylococcus aureus More Likely To Become Colonized or Infected with Methicillin-Resistant Staphylococcus aureus on Admission to a Hospital?

Abstract: Of 840 patients at hospital admission, 2.7% were positive for methicillin-resistant Staphylococcus aureus (MRSA) and 22.3% were positive for methicillin-susceptible S. aureus (MSSA). During the next 8 months, 4.8% of the MSSA-positive patients acquired MRSA with no lineage association. A total of 5.2% of noncarriers acquired MRSA. We find no evidence that colonized hosts are more susceptible to acquiring MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…All infection isolates were from blood culture bottles of patients with clinical symptoms of bacteraemia. Colonization isolates were from routine nasal specimens taken for MRSA screening purposes at admission to the same hospital in 2009 (n516) (Krebes et al, 2011). Two sequenced isolates were also included: MRSA5096 (CC22) and MRSA252 (CC30) (Holden et al, 2004) Whole genome DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…All infection isolates were from blood culture bottles of patients with clinical symptoms of bacteraemia. Colonization isolates were from routine nasal specimens taken for MRSA screening purposes at admission to the same hospital in 2009 (n516) (Krebes et al, 2011). Two sequenced isolates were also included: MRSA5096 (CC22) and MRSA252 (CC30) (Holden et al, 2004) Whole genome DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The few published studies have shown contradictory results. 17,18 For instance, Krebes et al 18 showed that noncarriers of MSSA were not more susceptible to acquiring MRSA compared with MSSA carriers. Among 840 included patients, 9 (21.4%) of 42 patients who acquired MRSA during their hospitalization versus 178 (23%) of 775 patients who did not acquire MRSA were MSSA carriers.…”
Section: Discussionmentioning
confidence: 99%
“…17 By contrast, a small retrospective study suggested that carriage of MSSA was not protective against MRSA acquisition. 18 Of note, both studies evaluated MRSA in the nares only.…”
Section: Does Colonization With Methicillin-susceptiblementioning
confidence: 99%
“…Consequently, the effect of prior colonization on S. aureus endo-versus exo-infection is unclear. It has been shown that patients re-admitted to the hospital benefitted from a protective effect of being colonised with MSSA [22,23]. The protective efficacy of such colonization in the prevention of acquisition of MRSA was calculated to be 78%.…”
Section: Introductionmentioning
confidence: 99%